Ni / Ce-C / CaO double-carrier composite catalyst, preparation method and application thereof

CN122875233APending Publication Date: 2026-10-09INNER MONGOLIA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611323284.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

因此,构建由碳材料和CaO组成的C/CaO双载体,并协同负载Ni元素和Ce元素,有望解决Ni基催化剂分散性不足、易积碳失活和产氢选择性不高等问题

Benefits of technology

[0039](1)本发明的Ni/Ce-C/CaO双载体复合催化剂,以C/CaO作为复合载体,利用Ni、Ce双金属协同改性,能显著提升催化剂在固废共气化制氢中的焦油裂解、蒸汽重整及水煤气变换反应活性,同时强化催化剂抗积碳性能,有效克服传统Ni基催化剂在高温水蒸气环境下易积碳、金属易烧结、活性位点被覆盖失活等缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875233A_ABST
    Figure CN122875233A_ABST
Patent Text Reader

Abstract

The application discloses a Ni / Ce-C / CaO double-carrier composite catalyst and a preparation method and application thereof. The catalyst is composed of a carbon material and CaO to form a C / CaO double carrier, Ni element is used as a main active component, and Ce element is used as a catalytic component. The composite catalyst is prepared through impregnation, drying, molding and calcination. The carbon material in the catalyst is favorable for improving the dispersity and mass transfer performance of the metal active component, the CaO can provide alkaline sites and in-situ adsorb CO2, the Ni element promotes tar cracking, light hydrocarbon steam reforming and water gas shift reaction, the Ce element improves the oxygen migration ability through Ce 3+ / Ce 4+ The reversible oxidation-reduction cycle improves the oxygen migration ability and simultaneously inhibits the generation of carbon deposition. Experiments show that when the catalyst is applied to the preparation of hydrogen-rich synthesis gas through the co-gasification of biomass and coal gangue, the volume fraction of H2 in the synthesis gas reaches 59.71%, and the total gas yield reaches 19.13 mmol / g. The catalyst has the advantages of high catalytic activity, good selectivity, carbon deposition resistance and strong raw material adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of solid waste resource utilization, catalytic gasification for hydrogen production and energy chemical technology, specifically relating to a Ni / Ce-C / CaO dual-support composite catalyst, its preparation method and application. Background Technology

[0002] Hydrogen energy is a clean and efficient energy carrier. Biomass gasification for hydrogen production can convert agricultural and forestry waste into hydrogen-rich syngas, which is an important technology for achieving low-carbon energy conversion. Corn stalks have the characteristics of high volatile content, strong reactivity, and wide availability, but they are prone to producing tar during gasification alone, and the alkali metals in the ash can easily cause slagging problems. Coal gangue is a large amount of solid waste generated during coal mining and washing. It contains silica-alumina mineral phases and a certain amount of fixed carbon, but its gasification activity alone is insufficient, and the quality of the gas produced is also low.

[0003] Existing technologies co-gasify corn stalks (CS) and coal gangue (CG), leveraging their complementary properties in volatile component release, mineral catalysis, heat transfer, and carbon conversion to alleviate slagging and tar problems in single-biomass gasification processes. However, relying solely on the synergistic effect between feedstocks is insufficient for the targeted production of hydrogen-rich syngas. Furthermore, the gasified volatile components contain large amounts of intermediate products such as tar, methane, and light hydrocarbons, necessitating highly efficient catalysts to further promote tar cracking, steam reforming, and water-gas shift reactions. Existing Ni-based catalysts possess strong C / C and CH bond breaking capabilities, effectively promoting the conversion of tar and light hydrocarbons to H2 and CO. However, Ni-based catalysts are prone to defects such as carbon deposition, sintering, and active site shielding under high-temperature steam atmospheres, leading to a decline in their catalytic performance.

[0004] CaO possesses strong alkalinity and CO2 adsorption capacity, which can drive the water-gas shift reaction and related equilibrium towards hydrogen production by capturing CO2 in situ; carbon materials have good pore structure and surface dispersion, which can provide a loading interface for metal components and improve mass transfer; Ce has excellent oxygen storage / release capacity. 3+ / Ce 4+ Reversible oxidation can enhance oxygen migration and promote the oxidation of carbon precursors. Therefore, constructing a C / CaO dual support composed of carbon materials and CaO, and synergistically loading Ni and Ce elements, is expected to solve the problems of insufficient dispersion, easy carbon deposition and deactivation, and low hydrogen production selectivity of Ni-based catalysts. Summary of the Invention

[0005] To address the problems existing in the prior art, this invention provides a Ni / Ce-C / CaO dual-support composite catalyst and its preparation method.

[0006] Another objective of this invention is to provide a method for preparing syngas using a Ni / Ce-C / CaO dual-support catalyst. The method uses corn stalks and coal gangue as raw materials, and the volatiles, tar and light hydrocarbons produced by co-gasification undergo cracking, steam reforming and water-gas shift reactions in the catalyst bed. This method can improve the volume fraction of H2 and the total gas yield.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] A Ni / Ce-C / CaO dual-supported composite catalyst, the catalyst comprising a dual support, an active metal, and a co-catalytic component; the dual support is a carbon material and CaO.

[0009] The active metal is Ni, and the co-catalytic component is Ce.

[0010] The content of Ni and Ce elements is 0-10 wt% of the total mass of the catalyst; the catalyst contains one or both of Ni and Ce elements, with the balance being a C / CaO dual support.

[0011] The Ni / Ce-C / CaO dual-support composite catalyst has Ni distributed on the surface of the dual support in the form of Ni, NiO, or a combination of both, and Ce distributed in the form of CeO2 and CeO2. 3+ / Ce 4+ Or in combination thereof, they are distributed on the surface of the dual carriers.

[0012] In this dual-carrier system, the mass ratio of carbon material to calcium oxide is 1:1, and the carbon material is one of activated carbon, semi-coke, or carbon black.

[0013] Preferably, the content of Ni and Ce elements accounts for 8 wt% and 4 wt% of the total mass of the catalyst, respectively.

[0014] A method for preparing the Ni / Ce-C / CaO dual-support composite catalyst includes the following steps:

[0015] S1. According to the target loading of Ni and Ce elements, weigh the corresponding amounts of Ni-containing precursor and Ce-containing precursor, mix them, add deionized water, and obtain impregnation solution A.

[0016] S2. Mix carbon materials and CaO in a 1:1 mass ratio to form a C / CaO dual carrier, and obtain a mixed solid B.

[0017] S3. Add the mixed solid B to the impregnation solution A and stir to obtain the impregnation solution C, so that Ni ions and Ce ions are evenly distributed on the surface and pores of the dual carrier.

[0018] S4. Dry the impregnation solution C to obtain solid D;

[0019] S5. Grind solid D to obtain powder E;

[0020] S6. Granulate powder E to obtain particles F;

[0021] S7. Place particle F in a muffle furnace and calcine at 750-950℃ for 2-5 hours. After cooling, obtain a Ni / Ce-C / CaO dual-support composite catalyst.

[0022] Preferably, the Ni-containing precursor is Ni(NO3)2·6H2O, and the Ce-containing precursor is Ce(NO3)3·6H2O; the stirring time in step S3 is 6-18 h.

[0023] Preferably, the drying temperature in step S4 is 80-120℃ and the drying time is 8-16 h; the calcination temperature in step S7 is 900℃ and the calcination time is 3 h.

[0024] A method for preparing hydrogen-rich syngas using a Ni / Ce-C / CaO dual-support composite catalyst includes the following steps:

[0025] (1) The corn stalks and coal gangue were crushed into powder, passed through a 40-mesh sieve, dried in a drying oven for 12 hours, and then mixed according to the set mass ratio to obtain a mixture;

[0026] The corn stalks in the mixture can provide active volatiles and alkaline earth metals, while the coal gangue has mineral catalysis and anti-slagging effects. The two form a synergistic effect in the reaction.

[0027] (2) The co-gasification experiment was carried out in a two-stage fixed-bed reactor. The experimental setup mainly included a gas supply system, a reaction system, a condensation and purification system, and a gas collection and detection system. The mixture was added to the pyrolysis zone of the fixed-bed reactor, and the Ni / Ce-C / CaO dual-support composite catalyst was added to the reforming zone of the fixed-bed reactor.

[0028] Synergistic modification with Ni and Ce bimetals helps to enhance the activity of catalysts in tar cracking, steam reforming, and water-gas shift reactions during co-gasification hydrogen production.

[0029] (3) Purge the reaction tube and fixed-bed reactor with nitrogen at a flow rate of 100 mL / min to remove the air; then heat the fixed reactor at a heating rate of 10℃ / min to make the temperature of the pyrolysis zone 800-900℃ and the temperature of the reforming zone 850-950℃; the influent flow rate during the reaction is 0.5-2.0 mL / min.

[0030] (4) During the reaction, the gas produced by catalytic cracking and reforming is collected after condensation, drying and purification to obtain syngas.

[0031] Preferably, the mass ratio of corn stalks to coal gangue is 5:5, the temperature of the pyrolysis zone is 850℃, the temperature of the reforming zone is 900℃, and the influent flow rate is 1.0 mL / min.

[0032] Preferably, the mass ratio of the mixture to the catalyst is 2:1.

[0033] Co-gasification reaction mechanism:

[0034] In the co-gasification process of corn stalks and coal gangue, the corn stalks first undergo pyrolysis, releasing volatile components, oxygen-containing organic intermediates, light hydrocarbons, and free radicals. The mineral components in the coal gangue promote secondary cracking of the volatile components, alleviating the slagging problem caused by gasification of corn stalks alone. The pyrolysis gas, tar, and light hydrocarbons enter the catalytic reforming zone along with nitrogen and steam.

[0035] In the catalyst bed, Ni / NiO provides active sites for the breaking of CC and CH bonds, promoting tar cracking, methane steam reforming, and light hydrocarbon reforming; water vapor dissociates at the active sites to generate -H and -OH active species, further promoting H2 generation.

[0036] CaO reacts with CO2 in a carbonation reaction to form CaCO3, thereby reducing the concentration of CO2 in the gas phase and driving the water-gas reaction towards the formation of H2. CeO2 contains Ce... 4+ It promotes the formation of oxygen vacancies and oxygen migration. Surface active oxygen reacts with carbon deposit precursors to generate CO, CO2 or H2O, reducing catalyst deactivation caused by carbon deposits.

[0037] The beneficial effects of this invention are:

[0038] Compared with the prior art, the present invention has the following advantages:

[0039] (1) The Ni / Ce-C / CaO dual-support composite catalyst of the present invention uses C / CaO as a composite support and utilizes the synergistic modification of Ni and Ce bimetals to significantly improve the catalyst’s activity in tar cracking, steam reforming and water-gas shift reaction in solid waste co-gasification hydrogen production. At the same time, it strengthens the catalyst’s anti-carbon deposition performance and effectively overcomes the defects of traditional Ni-based catalysts such as easy carbon deposition, easy metal sintering and active site deactivation under high temperature steam environment.

[0040] (2) The dual-support catalyst of the present invention can be used for the co-gasification reaction of corn stalks and coal gangue. The optimal catalytic process parameters were determined through experiments: Ni loading of 8 wt% and Ce loading of 4 wt%; the mass ratio of corn stalks to coal gangue raw materials was 5:5; the temperature of the pyrolysis zone was 850℃, the temperature of the catalytic reforming zone was 900℃, and the influent flow rate was 1.0 mL / min. The highest H2 volume fraction in the syngas could reach 59.71%, and the highest total gas production rate could reach 19.13 mmol / g, with a significant improvement in both the hydrogen content and the overall gas production performance.

[0041] (3) This invention utilizes corn stalks and coal gangue to prepare hydrogen-rich syngas, which not only realizes the high-value utilization of agricultural waste and coal gangue, but also reduces tar by-products and improves the quality of syngas, and has excellent prospects for industrial promotion.

[0042] (4) The Ni / Ce-C / CaO dual-support composite catalyst of the present invention has a wide range of applications and can be adapted to the catalytic gasification and pyrolysis gas reforming processes of agricultural and forestry waste, coal-based solid waste and various carbon-containing solid raw materials. Attached Figure Description

[0043] Figure 1 This invention relates to the composition and yield of syngas under different mass ratios of coal gangue / corn stalks; where a represents the composition of each component of syngas under different mass ratios of coal gangue / corn stalks, b represents the gas yield under different mass ratios of coal gangue / corn stalks, the bar chart represents the yield of each gas in the syngas, and the line graph represents the total gas yield.

[0044] Figure 2 The diagram shows the composition and yield of the synthesis gas of the catalyst of the present invention under different Ni loading conditions.

[0045] Where a represents the gas composition of Ni-C catalysts with different Ni loadings, b represents the gas yield of Ni-C catalysts with different Ni loadings, c represents the gas composition of Ni-C / CaO catalysts with different Ni loadings, and d represents the gas yield of Ni-C / CaO catalysts with different Ni loadings; the bar charts in figures b and d represent the yield of each gas in the synthesis gas, and the line chart represents the total gas yield.

[0046] Figure 3 The diagram shows the composition and yield of syngas under different Ce loading conditions for the catalyst of the present invention; where a represents the composition of each component of syngas under different Ce loading conditions, b represents the gas yield under different Ce loading conditions, the bar chart represents the yield of each gas in the syngas, and the line chart represents the total gas yield.

[0047] Figure 4The diagram shows the gas composition and yield of the synthesis gas preparation reaction under different reforming temperatures and feed water flow rates in this invention; where a represents the composition of each component of the synthesis gas at different reforming temperatures, b represents the gas yield at different reforming temperatures, c represents the composition of each component of the synthesis gas at different feed water flow rates, and d represents the gas yield at different feed water flow rates. The bar charts in figures b and d represent the yield of each gas in the synthesis gas, and the line chart represents the total gas yield.

[0048] Figure 5 The images show the XRD patterns of catalysts with different Ni and Ce loadings according to the present invention; where a is the XRD pattern of Ni-C / CaO dual-support composite catalysts with different Ni loadings, and b is the XRD pattern of Ni / Ce-C / CaO dual-support composite catalysts with different Ce loadings.

[0049] Figure 6 The images show the SEM morphology of different catalysts used in this invention. In the images, a represents biochar, b represents an 8% Ni-C catalyst, c represents an 8% Ni-C / CaO catalyst, d represents a 2% Ce / 8% Ni-C / CaO catalyst, e represents a 4% Ce / 8% Ni-C / CaO catalyst, and f represents a 10% Ce / 8% Ni-C / CaO catalyst.

[0050] Figure 7 The results are the BET pore structure analysis results of the catalyst of this invention.

[0051] Figure 8 The above are XPS spectra of the catalyst of this invention, where a is the O 1s spectrum, b is the Ni 2p spectrum, and c is the Ce 3d spectrum. Detailed Implementation

[0052] The technical solution of the present invention will be further described in detail below with reference to the embodiments.

[0053] Example 1: Preparation of Ni / Ce-C / CaO dual-support composite catalyst

[0054] 1. Composition of the catalyst: It includes a dual support, an active metal component, and a co-catalytic component; the dual support is activated carbon and calcium oxide, the active metal component is Ni, and the co-catalytic component is Ce; based on the total mass of the catalyst, the mass content of Ni is 1-10 wt%, the mass content of Ce is 1-10 wt%, and the balance is C / CaO dual support.

[0055] 2. Preparation method:

[0056] S1. Based on the target loading of Ni and Ce, weigh out the required amounts of Ni(NO3)2·6H2O and Ce(NO3)3·6H2O respectively, mix them, add deionized water, and prepare a metal salt impregnation solution.

[0057] S2. Mix activated carbon and CaO in a 1:1 mass ratio to form a C / CaO dual carrier.

[0058] S3. Add the C / CaO dual carrier to the above metal salt impregnation solution and impregnate for 12 h with magnetic stirring to make Ni ions and Ce ions uniformly distributed on the surface and in the pores of the dual carrier.

[0059] S4. Place the impregnated mixture in an oven and dry it at 80-120℃ for 8-16 h. After drying, grind and granulate to obtain spherical or granular catalyst.

[0060] S5. Subsequently, the catalyst was placed in a muffle furnace and calcined at 900℃ for 3 h. After cooling, a Ni / Ce-C / CaO dual-support composite catalyst was obtained.

[0061] Example 2: Co-gasification reaction of corn stalks and coal gangue

[0062] (1) The raw materials are corn stalks (CS) and coal gangue (CG). The corn stalks and coal gangue are crushed into powder, passed through a 40-mesh sieve, and dried in a drying oven for 12 h. The two are mixed according to the set mass ratio to obtain mixed raw materials.

[0063] (2) The co-gasification experiment was carried out in a two-stage fixed-bed reactor. The experimental setup mainly included a gas supply system, a reaction system, a condensation and purification system, and a gas collection and detection system. The mixed raw materials were added to the pyrolysis zone, and the Ni / Ce-C / CaO dual-support composite catalyst of Example 1 was placed in the reforming zone; the mass ratio of the mixed raw materials to the catalyst was 2:1.

[0064] (3) Before the reaction, purge the reaction tube and fixed bed reactor with N2 for 30 min at a flow rate of 100 mL / min to remove air. Then heat the reactor to the set temperature at a heating rate of 10℃ / min. The temperature of the pyrolysis zone is 800-900℃, the temperature of the reforming zone is 850-950℃, and the inlet water flow rate is 0.5-2.0 mL / min.

[0065] (4) The gas produced by the co-gasification reaction is collected after condensation, drying and purification to obtain hydrogen-rich synthesis gas.

[0066] (5) The composition and content of hydrogen-rich synthesis gas were analyzed by gas chromatography, including H2, CO, CO2, CH4 and C. n H m Gas components, etc.

[0067] Example 3: Effect of syngas feedstock ratio on co-gasification reaction

[0068] Following the method of Example 1, a Ni-C / CaO dual-support composite catalyst with an 8 wt% Ni loading was prepared. Following the syngas preparation steps of Example 2, with the pyrolysis zone temperature at 850°C, the reforming zone temperature at 900°C, the influent water flow rate at 1.0 mL / min, and the feedstock CG:CS mass ratios of 10:0, 7:3, 5:5, 3:7, and 0:10, the effects of different feedstock ratios on the composition and yield of the syngas were investigated.

[0069] The experimental results are shown in Figure 1 As the proportion of corn stalks increased, the total gas yield showed an upward trend, indicating that the high volatile components of corn stalks are conducive to gas release; however, the H2 volume fraction showed a downward trend, indicating that coal gangue plays a positive role in maintaining a high H2 selectivity.

[0070] When CG:CS = 5:5, a better balance is achieved between the H2 volume fraction and the total gas yield. At this ratio, corn stalks provide a source of active volatiles and alkaline earth metal migration, while coal gangue provides mineral catalysis and anti-slagging effects. The two form a synergistic effect in terms of free radical intermediates, pore structure, and redox cycle.

[0071] Example 4: Effect of Ni loading on catalytic performance

[0072] Following the method of Example 1, Ni-C / CaO dual-support composite catalysts with Ni loadings of 0, 2, 4, 6, 8, and 10 wt% were prepared. Following the steps of Example 2, the effect of Ni loading in the catalyst on gas composition and yield was investigated under the conditions of CG:CS = 5:5, pyrolysis zone temperature 850℃, reforming zone temperature 900℃, and feed water flow rate 1.0 mL / min.

[0073] Experimental results are as follows Figure 2 As shown, as the Ni loading of the catalyst increases from 0 to 8 wt%, the volume fraction of H2, the yield of H2, and the total gas yield all show an increasing trend, indicating that the catalyst can effectively promote tar cracking, methane steam reforming, and secondary conversion of light hydrocarbons.

[0074] Compared to a Ni loading of 8 wt%, the total gas yield and H2 yield decrease when the Ni loading reaches 10 wt%. This is likely because excess Ni in the catalyst can cause particle agglomeration, sintering, or pore blockage, reducing the number of exposed active sites. Therefore, a Ni loading of 8 wt% is preferred in the catalyst.

[0075] Example 5: Effect of Ce loading on catalytic performance

[0076] Following the steps of Example 1, with the Ni loading fixed at 8 wt%, Ni / Ce-C / CaO dual-support composite catalysts were prepared by setting the Ce loading to 2, 4, 6, 8, and 10 wt%.

[0077] Following the steps of Example 2, the co-gasification reaction was carried out under the conditions of CG:CS=5:5, pyrolysis zone temperature 850℃, reforming zone temperature 900℃, and feed water flow rate 1.0 mL / min. The effect of Ce loading on the performance of Ni-C / CaO catalyst was investigated.

[0078] The experimental results are shown in Figure 3 When the Ce loading increased from 2 wt% to 4 wt%, the volume fraction of H2 in the syngas increased from 58.09% to 59.71%, and the total gas yield reached 19.13 mmol / g (based on a mixture of corn stalks and coal gangue). This indicates that an appropriate amount of Ce in the catalyst can improve the dispersibility of Ni, the oxygen vacancy concentration, and the content of surface active oxygen, thereby promoting tar cracking, steam reforming, and water-gas shift reactions.

[0079] As the Ce loading in the catalyst continues to increase, the H2 volume fraction begins to decrease relative to a 4 wt% Ce loading, indicating that excess Ce may form CeO2 aggregates or cover some Ni active sites, leading to restricted pore structure and reduced active site utilization. Therefore, the preferred Ce loading in the catalyst is 4 wt%.

[0080] Example 6: Effects of reforming temperature and feed water flow rate on co-gasification reaction

[0081] An 8%Ni / 4%Ce-C / CaO dual-support composite catalyst with a Ni element loading of 8 wt% and a Ce element loading of 4 wt% was prepared according to the steps of Example 1.

[0082] Hydrogen production was carried out by co-gasification according to the steps of Example 2. Under the conditions of pyrolysis zone temperature of 850°C and water flow rate of 1.0 mL / min, the reforming temperature was set to 850, 900 and 950°C respectively, and the effect of reforming temperature on gas production performance was investigated.

[0083] See results Figure 4 a and 4b show that when the reforming temperature is increased from 850℃ to 900℃, the volume fraction of H2 increases from 50.35% to 59.71%, and the total gas yield increases to 19.13 mmol / g, reaching a relatively optimal level. When the reforming temperature continues to increase to 950℃, the volume fraction of H2 gradually decreases, which may be related to the sintering of the metal components.

[0084] Under the same catalyst conditions, following the steps of Example 2, and with the pyrolysis zone temperature at 850°C and the reforming zone temperature at 900°C, the influent flow rate was set to 0, 1, and 2 mL / min, respectively, to investigate the effect of the influent flow rate on gas production performance. The results are shown below. Figure 4 c. On day 4, when the influent flow rate increased from 0 to 1.0 mL / min, the H2 volume fraction significantly increased from 28.98% to 59.71%, while when the influent flow rate increased from 1.0 mL / min to 2 mL / min, the H2 volume fraction and total gas yield decreased slightly. This indicates that an appropriate amount of steam can enhance steam gasification, methane steam reforming, and water-gas shift reaction. When the influent flow rate continued to increase, the H2 volume fraction tended to decrease, which is due to the enhanced reverse water-gas shift reaction. Therefore, a reforming temperature of 900℃ and an influent flow rate of 1.0 mL / min are preferred.

[0085] Example 7: Catalyst Structure Characterization and Mechanism of Action

[0086] The unused fresh catalysts prepared in Examples 4 and 5 were used for structural characterization and analysis.

[0087] XRD results are as follows Figure 5 As shown, a is the XRD pattern of the Ni-C / CaO dual-support composite catalyst with different Ni loading in Example 4, and b is the XRD pattern of the Ni / Ce-C / CaO dual-support composite catalyst with different Ce loadings and Ni loading of 8% in Example 5, and the Ni-C / CaO dual-support composite catalyst with 8% Ni loading in Example 4.

[0088] Figure 5 In section a, the catalysts corresponding to the curves from top to bottom are: 10% Ni-C / CaO, 8% Ni-C / CaO, 6% Ni-C / CaO, 4% Ni-C / CaO, and 2% Ni-C / CaO.

[0089] Figure 5 In b, the catalysts corresponding to the curves from top to bottom are:

[0090] 8%Ni / 10%Ce-C / CaO, 8%Ni / 8%Ce-C / CaO, 8%Ni / 6%Ce-C / CaO, 8%Ni / 4%Ce-C / CaO, 8%Ni / 2%Ce-C / CaO, 8%Ni / 0%Ce-C / CaO.

[0091] Figure 5 As can be seen from a, there are crystalline phases such as CaO, Ca(OH)2, NiO and CeO2 in the catalyst; as the Ni loading increases, the NiO-related diffraction peaks are enhanced; when the Ni loading is too high, Ni is prone to agglomeration.

[0092] Figure 5As can be seen from b, the CeO2 diffraction peaks are enhanced with the increase of Ce loading; an appropriate amount of Ce helps to improve the dispersion state of Ni.

[0093] Figure 6 The SEM images of different substances show that 4% Ce can effectively regulate the microstructure of the catalyst and build a well-developed pore structure; while excessive Ce will lead to particle agglomeration and pore blockage, which provides a basis for optimizing the Ce loading of the catalyst.

[0094] Figure 6 In the diagram, a represents biochar, b represents 8% Ni-C catalyst, c represents 8% Ni-C / CaO catalyst, d represents 2% Ce / 8% Ni-C / CaO catalyst, e represents 4% Ce / 8% Ni-C / CaO catalyst, and f represents 10% Ce / 8% Ni-C / CaO catalyst.

[0095] from Figure 6 It can be seen that the pure carbon support exhibits a smooth, dense blocky structure with no obvious porous features (see...). Figure 6 a) After loading with 8% Ni, the carbon surface changed from a smooth surface to a rough, granular aggregate, indicating that metallic Ni was successfully loaded and altered the surface properties of the carbon (see...). Figure 6 b) After the introduction of CaO, the particle size of the 8% Ni-C / CaO catalyst was further reduced, the agglomeration between particles was alleviated, and a more uniform flocculent stacking structure was formed (see...). Figure 6 c).

[0096] With increasing Ce doping concentration, the catalyst morphology exhibits a regular change: at 2% Ce doping ( Figure 6 d), obvious spherical particle agglomeration appears on the surface, and the pore structure is relatively well-developed; when the Ce content increases to 4% ( Figure 6 e), the particles fuse to form a continuous, dense framework, with obvious pores appearing on the surface, which is direct morphological evidence of increased pore volume; when the Ce content is too high (10%), Figure 6 f) The catalyst surface exhibits a dense, lamellar coating structure, with the interparticle gaps completely filled, leading to pore blockage. This may be the main reason for the decline in catalytic performance caused by high Ce content.

[0097] The above analysis shows that the doping amount of 4% Ce can effectively control the microstructure of the catalyst and build a well-developed pore structure; while excessive Ce will lead to particle agglomeration and pore blockage, which provides a basis for optimizing the Ce loading of the catalyst.

[0098] BET results are as follows Figure 7 As shown in the figure, the isothermal adsorption-desorption curves of 8% Ni / 4% Ce-C / CaO before and after the use of the optimal catalyst are shown. The total pore volume of the sample increased by about 166.4% after the reaction.

[0099] The results showed that Ce modification promoted pore expansion and mesoporous structure reconstruction during the reaction process, significantly increasing the total pore volume, and the newly formed pores were mainly of larger diameter.

[0100] The C / CaO dual support provides the catalyst with a porous structure and a loading interface. The introduction of an appropriate amount of Ce improves the catalyst's pore structure, facilitating the diffusion of volatile components and tar molecules, and increasing the exposure of active sites.

[0101] XPS results are as follows Figure 8 As shown, the spectra include O 1s, Ni 2p and Ce 3d, corresponding to Figures a, b and c, respectively.

[0102] Figure 8 In the figure, a to c are the high-resolution XPS fitted spectra of O 1s, Ni 2p and Ce 3d on the catalyst surface, respectively, used to analyze the changes in oxygen species and metal element valence states on the catalyst surface before and after the reaction. The horizontal axis is the binding energy in eV, and the vertical axis is "intensity / au" which represents the relative signal intensity.

[0103] Figure 8 As shown in section a, the O 1s spectrum consists of three main components: low binding energy, medium binding energy, and high binding energy components, with their peak center binding energies located at approximately 529.7–530.2 eV, 531.2–531.7 eV, and 532.8–534.0 eV, respectively. The low binding energy component (Olatt) is attributed to lattice oxygen. The medium binding energy component (Oabs) is mainly attributed to the overlapping contributions of surface hydroxyl groups, defect-related oxygen species, adsorbed oxygen, and carbonate-related oxygen species. The high binding energy component (Oads) is primarily related to adsorbed water and oxygen-containing functional groups on the carbon support.

[0104] After the reaction, the Oabs peak of 8Ni / C-CaO weakened while the Olatt peak strengthened, indicating a redistribution of surface oxygen. The addition of Ce further altered this distribution, and the weakening of the Oabs peak and the strengthening of the Olatt peak in the used 4%Ce / 8%Ni-C / CaO indicated changes in adsorbed oxygen and lattice oxygen species.

[0105] Figure 8 The Ni 2p spectrum in the middle b region shows that the coexistence of these main peaks and satellite peaks indicates that the nickel species on the catalyst surface are mainly Ni. 2+ It exists in the form of [missing information]. Based on XRD results, this species was identified as NiO. After the reaction, the surface atomic fraction of nickel decreased, which is likely due to surface reconstruction and partial coverage by reaction intermediates and coke precursors.

[0106] Figure 8 The 3D spectrum of Ce in the middle c part shows Ce 3+and Ce 4+ The coexistence indicates that the Ce species on the surface are in a mixed oxidation state. The ratio of Ce valence states in the catalyst changes before and after the reaction; before the reaction, Ce... 3+ / Ce 4+ The peak area ratio was 1.75, which decreased to 0.51 after catalytic reaction, indicating that Ce... 3+ The active sites are involved in oxygen migration, and some Ce... 3+ Oxidized to Ce 4+ , forming dynamic Ce 3+ / Ce 4+ The redox cycle enhances the oxygen transfer capacity of the catalyst.

[0107] Depend on Figure 8 It can be seen that the catalytic mechanism of the Ni / Ce-C / CaO dual-support composite catalyst of the present invention is as follows: Ni element provides active sites for tar cracking and steam reforming; CaO drives the reaction equilibrium towards hydrogen production by in-situ capturing CO2; Ce element promotes the reaction equilibrium towards hydrogen production through Ce... 3+ / Ce 4+ Cyclic and oxygen vacancies promote the oxidative transformation of intermediates and inhibit carbon deposition; carbon materials improve metal dispersion and mass transfer properties.

[0108] The process parameters for the catalytic reaction of the present invention were obtained through the above embodiments, as shown in Table 1.

[0109] Table 1 Co-gasification reaction parameters

[0110]

Claims

1. A Ni / Ce-C / CaO dual-support composite catalyst, characterized in that, The catalyst comprises a dual support, an active metal, and a co-catalytic component; the dual support is a carbon material and calcium oxide, the active metal is Ni, and the co-catalytic component is Ce. The content of Ni and Ce elements is 0-10 wt% of the total mass of the catalyst; the catalyst contains one or both of Ni and Ce elements.

2. The Ni / Ce-C / CaO dual-support composite catalyst according to claim 1, characterized in that, Ni is distributed on the dual-support surface in the form of Ni, NiO, or a combination of both, while Ce is distributed in the form of CeO2 and Ce. 3+ / Ce 4+ Or in combination thereof, they are distributed on the surface of the dual carriers.

3. The Ni / Ce-C / CaO dual-support composite catalyst according to claim 1 or 2, characterized in that, The mass ratio of carbon material to calcium oxide in the dual carrier is 1:

1. The carbon material is one of activated carbon, semi-coke, and carbon black. The content of Ni and Ce elements is 8 wt% and 4 wt% of the total mass of the catalyst, respectively.

4. A method for preparing the Ni / Ce-C / CaO dual-support composite catalyst as described in any one of claims 1-3, characterized in that, Includes the following steps: S1. According to the target loading of Ni and Ce elements, weigh the corresponding amounts of Ni-containing precursor and Ce-containing precursor, mix them, add deionized water, and obtain impregnation solution A. S2. Mix carbon materials and CaO in a 1:1 mass ratio to form a C / CaO dual carrier, and obtain a mixed solid B. S3. Add the mixed solid B to the impregnation solution A and stir to obtain the impregnation solution C; S4. Dry the impregnation solution C to obtain solid D; S5. Grind solid D to obtain powder E; S6. Granulate powder E to obtain particles F; S7. Place particle F in a muffle furnace and calcine at 750-950℃ for 2-5 hours. After cooling, obtain the Ni / Ce-C / CaO dual-support composite catalyst.

5. The method according to claim 4, characterized in that, The Ni-containing precursor in step S1 is Ni(NO3)2·6H2O, and the Ce-containing precursor is Ce(NO3)3·6H2O; the stirring time in step S3 is 6-18 h.

6. The method according to claim 4, characterized in that, The drying temperature in step S4 is 80-120℃ and the drying time is 8-16 h; the calcination temperature in step S7 is 900℃ and the calcination time is 3 h.

7. A method for preparing hydrogen-rich syngas using the Ni / Ce-C / CaO dual-support composite catalyst according to any one of claims 1-3, characterized in that, The method includes the following steps: (1) The corn stalks and coal gangue were crushed into powder, passed through a 40-mesh sieve, dried in a drying oven for 12 hours, and then mixed according to the set mass ratio to obtain a mixture; (2) Add the mixture to the pyrolysis zone of the fixed-bed reactor and add the Ni / Ce-C / CaO dual-support composite catalyst to the reforming zone of the fixed-bed reactor; (3) Purge the reaction tube and fixed-bed reactor with nitrogen at a flow rate of 100 mL / min to remove the air; then heat the fixed reactor at a heating rate of 10℃ / min to make the temperature of the pyrolysis zone 800-900℃ and the temperature of the reforming zone 850-950℃; the influent flow rate during the reaction is 0.5-2.0 mL / min. (4) During the reaction, the gas produced by catalytic cracking and reforming is collected after condensation, drying and purification to obtain syngas.

8. The method according to claim 7, characterized in that, The mass ratio of corn stalks to coal gangue is 5:5, the temperature of the pyrolysis zone is 850℃, the temperature of the reforming zone is 900℃, and the influent flow rate is 1.0 mL / min.

9. The method according to claim 7, characterized in that, The mass ratio of the mixture to the catalyst is 2:1.